RELIGIOUS EDUCATION BASED MULTICULTURALISME IN VIEW OF MUHAMMAD FETHULLAH GULEN - M. Khoirul Hadi al-Asya'ari (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2015)
Research is a research-based Library Research, which is based on the reading of the literature on Fethullah Gulen, this research wants to reveal about the importance of education based on the multicultural, multicultural education in this paper pick-tentak Fethullah Gulen figure that gives an integral view of religion and public education, in this paper will show some results of the first study, that multicultural education is important in the effort menghalu radicalism, Fethullah Gulen's second try to give a new reading of Islamic religious education toward a more Humanist and egalitarian, the third understanding of multicultural education is taken from the understanding of the Qur'an.